Impact of ICT adoption on academic performance of students: evidence from the universities of Balochistan - Shah, Asadullah (Mazedan International Research Academy, 2022)
Because of universities' usage of ICT, students' academic achievement is assessed. There are a number of variables that influence the relationship between ICT use at school and academic achievement, including students' GPA and gender. In three Balochistan universities, quantitative research methodologies and a sample of 500 students were used to examine the relationship between ICT use and student performance. Structural equation modelling was used to test the validity of the research model. Structured equation modelling and route analysis were carried out using AMOS, a tool built expressly for this purpose. In a conservative society, the correlation between ICT usage and academic success is clear. According to an additional research, women's academic performance was also increased by the usage of ICT. IT degrees have minimal influence on student academic achievement, though. The study's conclusions, limitations, and suggestions for further research are all included. Finally, the outcomes of this investigation have implications for the current body of knowledge.